Understanding voter heterogeneity: an integrated psychological framework - De Santis, Lavinia; Morini, Mara (Frontiers in Political Science, 2025)
This paper builds on a comprehensive review of the main studies examining differences between right- and left-wing voters. Specifically, it identifies six key dimensions underlying these differences (personality; cognition; motivation; emotionality; social attitudes and group perception; time perspective) and advances the need to apply a mixed-method approach to assess them. By integrating existing insights with a multidimensional approach, the study seeks to provide a more systematic understanding of the psychological and ideological traits that distinguish voters across the political spectrum.